Prodromus of a fern flora for Bolivia. XXIX. Aspleniaceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2018)
We provide a synopsis of the family Aspleniaceae in Bolivia, including 88 species in four genera: Asplenium with 81 species, Desmophlebium with one, Hemidictyum with one, and Hymenasplenium with five. Desmophlebium and Hemidictyum have also been treated in distinct families, Desmophlebiaceae and Hemidictyaceae, respectively. Five species of Asplenium and one of Hymenasplenium are endemic to Bolivia.